Anti-apoptotic and Matrix Remodeling Actions of a Small Molecule Agonist of the Human Relaxin Receptor, ML290 in Mice With Unilateral Ureteral Obstruction - Ng, Hooi Hooi; Soula, Mariluz; Rivas, Bryan; Wilson, Kenneth J.; Marugan, Juan J.; Agoulnik, Alexander I. (Frontiers in Physiology, 2021)
Diseases, such as diabetes and hypertension, often lead to chronic kidney failure. The peptide hormone relaxin has been shown to have therapeutic effects in various organs. In the present study, we tested the hypothesis that ML290, a small molecule agonist of the human relaxin receptor (RXFP1), is able to target the kidney to remodel the extracellular matrix and reduce apoptosis induced by unilateral ureteral obstruction (UUO). UUO was performed on the left kidney of humanized RXFP1 mice, where the right kidneys served as contralateral controls. Mice were randomly allocated to receive either vehicle or ML290 (30 mg/kg) via daily intraperitoneal injection, and kidneys were collected for apoptosis, RNA, and protein analyses. UUO significantly increased expression of pro-apoptotic markers in both vehicle- and ML290-treated mice when compared to their contralateral control kidneys. Specifically, Bax expression and Erk1/2 activity were upregulated, accompanied by an increase of TUNEL-positive cells in the UUO kidneys. Additionally, UUO induced marked increase in myofibroblast differentiation and aberrant remodeling on the extracellular matrix. ML290 suppressed these processes by promoting a reduction of pro-apoptotic, fibroblastic, and inflammatory markers in the UUO kidneys. Finally, the potent effects of ML290 to remodel the extracellular matrix were demonstrated by its ability to reduce collagen gene expression in the UUO kidneys. Our data indicate that daily administration of ML290 has renal protective effects in the UUO mouse model, specifically through its anti-apoptotic and extracellular matrix remodeling properties.